IMPLEMENTASI PERDA NOMOR 9 TAHUN 2016 DALAM MEWUJUDKAN BUMNAG DI KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Netrivianti Netrivianti; Sayid Anshar; Ahmad Sadayu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Village Owned Enterprises are Village Enterprises formed or established by the Village Government whose capital ownership and management are carried out by the Village Government and the Community. The case study found in this study is that there has been no realization from the government that it has a plan that village income is sourced from the State Budget of 1 billion in Nagari Sungai Aur, Sungai Aur District, West Pasaman Regency and Nagari-Owned Enterprises (BUMNAG) in Sungai Aur District, Kabupapten West Passage. The purpose of this study was to find out the Implementation, Constraints and Efforts of PERDA Number 9 of 2016 in realizing BUMNAG in Sungai Aur District, West Pasaman Regency. Nagari Owned Enterprises are organized by each Nagari Government based on the origin of the Nagari in the West Sumatra Province Region which is under the system of Government of the Unitary State of the Republic of Indonesia.